A digital plan for elderly institutions: a preliminary survey (Revista Brasileira de Ciências do Envelhecimento Humano, 2022)
Portugal is one of the oldest countries in Europe and the World. About info-exclusion, all national and international studies report that the elderly is the most info-excluded social group. The pandemic that we are still experiencing has made confinement measures quite restrictive at the level of institutions for the elderly. Isolation worsened and socio-emotional disturbances worsened the quality of life of the elderly. This preliminary study aimed to investigate the existence of a digital plan that can reverse these constraints. From the focus groups carried out in three institutions for the elderly in the district of Castelo Branco (Portugal) with directors, caregivers, psychologists, and physical activity therapists, they showed a great lack of knowledge regarding the digital area for the elderly. The researchers presented some suggestions in the focus groups that were accepted: a robust Wi-Fi network for the entire institution; digital training for staff in apps related to cognitive training, motor training and social networks; apps related to video calls; creation of a digital space in the institution so that all seniors can access and use digital resources for free.